From Leadership to Agility: What, How and Where We Are Now? - I Gusti Ketut Gede; I Ketut Yasa; I Gusti Ngurah Sanjaya (Journal of International Conference Proceedings, 2022)
The role of leadership has become an important topic in the business, management and strategic literature. However, the important role of leadership in building organizational agility is still separate and has not been incorporated into the existing literature. The present study identifies the trend of research and publications in the Web of Science and Scopus database in the last two decades which were analyzed using a systematic literature review approach. The results show that at present, both topics are very important publication ideas, especially how organizations deal with turbulence from markets, competitors and even pandemics. Furthermore, the trend of publications regarding leadership in building organizational agility is increasing both in the number of publications, topic selection, impact factors, citations and author country networks. This review literature study provides a comprehensive overview of future leadership to build organizational agility research and collaboration opportunities.Â Keywords: Bibliometrics analysis, leadership, organizational agility, VoSViewer